2000
DOI: 10.1063/1.480683
|View full text |Cite
|
Sign up to set email alerts
|

The strong field photoelectron spectroscopy of acetylene: Evidence for short-lived 4p gerade states via electric field-induced resonance-enhanced multiphoton ionization

Abstract: We report the intense field photoelectron spectra of acetylene, excited using 780 nm, 135 fs radiation for intensities ranging from 5.7 to 8.6ϫ10 13 W cm Ϫ2. Three features observed at 1.59, 1.95, and 2.13 eV are repeated at higher energies throughout the spectra as above threshold ionization features. A method for analysis of the spectra and assignment of peaks is presented, based on intensity dependent shifting of intermediate states and ponderomotive shifts of the ionization potential. We present evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…1 The resonance enhanced multi-photon ionization photoelectron spectroscopy (REMPI-PS) has proven to be an excellent tool to study the photo-ionization and -dissociation dynamical process of the excited states. [2][3][4][5][6][7][8][9][10] In resonance enhanced multi-photon ionization process, REMPI-PS allows for the determination of the excited states in which the electrons are created, which offers valuable information on the electronic and vibrational characteristics in the excited states. Moreover, REMPI-PS can also identify the dynamical processes occurring in the excited states, which can determine the electrons deriving from the ionization of the neutral fragments or the dissociation of molecular ion.…”
mentioning
confidence: 99%
“…1 The resonance enhanced multi-photon ionization photoelectron spectroscopy (REMPI-PS) has proven to be an excellent tool to study the photo-ionization and -dissociation dynamical process of the excited states. [2][3][4][5][6][7][8][9][10] In resonance enhanced multi-photon ionization process, REMPI-PS allows for the determination of the excited states in which the electrons are created, which offers valuable information on the electronic and vibrational characteristics in the excited states. Moreover, REMPI-PS can also identify the dynamical processes occurring in the excited states, which can determine the electrons deriving from the ionization of the neutral fragments or the dissociation of molecular ion.…”
mentioning
confidence: 99%
“…The other is ionization of a molecule via its Rydberg states. Unlike Freeman resonance of atoms and some very small molecules, 10,11 earlier works have suggested that the detection of these states results from the internal conversion (IC) of so-called super excited states. 12 The mechanism only requires that a Rydberg state is populated, from which the ionization occurs via one or multi-photon absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Resonance-enhanced multiphoton-ionization (REMPI) photoelectron spectroscopy has been proven to be a wellestablished method to study the excited-state or Rydbergstate structure and the photoionization or photodissociation dynamical process [12][13][14][15][16][17][18]. The femtosecond laser pulse is an excellent tool to create the REMPI photoelectron spectroscopy because of its broad laser spectrum and high pulse intensity, while a main drawback for the femtosecondinduced REMPI photoelectron spectroscopy is low spectral resolution due to the broadband photoelectron spectrum.…”
mentioning
confidence: 99%